Phytochemical analysis of Hibiscus rosa-sinesis and its biomedical application - Madhura Joshi; Manali Deshmukh; Ashwattha Kamble; Amol Jadhav; Avinash Survase; Bandu Pawar (The Bioscan, 2025)
Hibiscus rosa-sinesis, belonging to the family Malvaceae, is a tropical and subtropical plant widely recognized for its medicinal properties. The plant can grow up to 2–5 meters, and its leaves are dark green, glossy, and ovate with serrated edges. Hibiscus rosa-sinesis has been traditionally used in various treatments because of its rich phytochemical content. The bioactive compounds in Hibiscus rosa-sinesis leaves, including flavonoids, tannins, alkaloids, phenolic compounds, terpenes, and saponins, have been extracted using the Soxhlet extraction method, with ethanol as a solvent. The leaves exhibit potent anti-inflammatory, antioxidant, antimicrobial, antifungal, and Antidiabetic properties, making the plant a significant candidate for biomedical applications. These properties allow the plant to be effective in treating infections, managing inflammation, and controlling oxidative stress and diabetes. The total phenolic content and total flavonoid content in the leaves of Hibiscus rosa-sinesis to assess their contribution to the plant’s medicinal potential. These phytochemicals are key contributors to the plant’s therapeutic efficacy, particularly in oxidative stress reduction and inflammatory response modulation.